The Effect Of High Performance Work Systems On Organizational Citizenship Behavior, With Psychological Well-Being, Organizational Commitment And Job Satisfaction As Intervening Variables - Truli Susatyo Dewi; Ferryal Abadi (Publikasi Indonesia, 2023)
The State Civil Apparatus (ASN) is required to have high performance. High Performance Work Systems (HPWS) can improve organizational and employee performance. This study aims to examine the effect of HPWS on Organizational Citizenship Behavior (OCB); find out how far Psychological Wellbeing (PWB) affects Job Satisfaction; and exploring PWB, Organizational Commitment and Job Satisfaction as a mediator for the HPWS-OCB relationship with ASN in 42 Regional Apparatus Organizations (OPD) DKI Jakarta Provincial Government. Determination of the sample by purposive sampling, with the criteria of an active civil servant who has worked for at least 1 year. Data collection used a survey, by distributing 33 questionnaires in the google-form via Whatsapp, to 185 respondents in June 2023. Data was analyzed using the Structural Equation Model Partial Least Square (SEM-PLS). The result is that HPWS has a significant positive effect on PWB and organizational commitment. The direct relationship between HPWS-OCB was positive but not significant, PWB was able to fully mediate positive HPWS-OCB. PWB has a significant positive effect on organizational commitment and will increase OCB. HPWS through PWB mediation and organizational commitment has a significant effect on job satisfaction, without HPWS mediation it has no significant effect on job satisfaction. Organizational commitment does not mediate the HPWS-OCB relationship and job satisfaction does not significantly affect OCB. The better government organizations implement HPWS in ASN management, the ASN's OCB will increase and ultimately lead to an increase in excellent service quality and organizational performance.